Pendidikan Anak Shaleh Perspektif Al-Zarnuji Dalam Kitab Ta’lim Muta’allim - Ayyub, Ayyub; Mardiana, Dina (Jurnal Ilmiah Global Education, 2024)
Children's education is carried out by cultivating good morals, protecting them from bad associations and is a way to get real life. This article discusses the education of pious children according to Al-Zarnuji in the book "ta'lim muta'allim", this book itself is a guide book for etiquette in teaching and learning which is studied in many educational institutions in Indonesia, from formal institutions to non-formal institutions. This research will describe and analyze the texts in the book "ta'lim muta'allim" which is a book that contains manners in studying Islam as well as a summary of the education of pious children. This article uses a qualitative approach with library research. This research found conclusions in accordance with the problems the author raised, namely as follows: 1) Most of Al-Zarnuji's advice regarding etiquette and procedures for studying are directly related to the pious education of children. 2) Al-Zarnuji's advice can be connected and proven practically and is very in accordance with the characteristics of a pious child in accordance with what Allah SWT exemplified and taught in the Koran and also taught Rasulullah SAW in his hadiths.